Can city-to-city cooperation facilitate sustainable development governance in the Global South? Lessons gleaned from seven North-South partnerships in Latin America. Issue 2 (4th May 2021) - Mayer, Luara; Nguyen Long, Le Anh
ABSTRACT: The search for mechanisms that can bolster sustainable development governance is underway. Bilateral city-to-city partnerships (C2C) have been put forward as platform through which cities can strengthen sustainable development in urban landscapes. Here, we critically examine claims about the capacity of these international cooperative arrangements, originally designed and deployed as development aid delivery mechanisms, to promote sustainable development. Our systematic examination of the extant literature on bilateral North-South C2C in Latin America fails to provide sufficient evidence that C2C can deliver on its promise to promote robust governance, both generally and in the specific context of sustainable development. Instead, it seems that C2C is more likely to support than challenge entrenched practices which can weaken sustainable development governance. Identifying these tendencies is a first step in formulating strategies that may enhance C2Cs and other transnational partnerships aimed at improving urban sustainable development in the Global South.